What have the revelations about Neanderthal DNA revealed about Homo sapiens? - Guimarães, Santiago Wolnei Ferreira; Silva, Hilton P. (Anthropological Review, 2020)
Genetic studies have presented increasing indications about the complexity of the interactions between Homo sapiens, Neanderthals and Denisovans, during Pleistocene. The results indicate potential replacement or admixture of the groups of hominins that lived in the same region at different times. Recently, the time of separation among these hominins in relation to the Last Common Ancestor – LCA has been reasonably well established. Events of mixing with emphasis on the Neanderthal gene flow into H. sapiens outside Africa, Denisovans into H. sapiens ancestors in Oceania and continental Asia, Neanderthals into Denisovans, as well as the origin of some phenotypic features in specific populations such as the color of the skin, eyes, hair and predisposition to develop certain kinds of diseases have also been found. The current information supports the existence of both replacement and interbreeding events, and indicates the need to revise the two main explanatory models, the Multiregional and the Out-of-Africa hypotheses, about the origin and evolution of H. sapiens and its co-relatives. There is definitely no longer the possibility of justifying only one model over the other. This paper aims to provide a brief review and update on the debate around this issue, considering the advances brought about by the recent genetic as well as morphological traits analyses.